Efektivitas Layanan Informasi tentang Terapi Musik Mozart dalam Mengurangi Kejenuhan Belajar Siswa Kelas VIII di SMP Islam Terpadu Al-Azhar Kota Jambi - nurhayati; Muhammad Ferdiansyah; Rully Andi Yaksa (STKIP Subang, 2025)
Learning boredom often becomes an obstacle that decreases students’ focus and motivation in the learning process. This study aims to determine the effectiveness of information services on Mozart music therapy in reducing learning boredom among eighth-grade students at SMP Islam Terpadu Al-Azhar Kota Jambi. The research used a quantitative experimental approach with a non-equivalent control group design. Samples were selected using purposive sampling, involving 20 students divided into an experimental and a control class. Data were collected using a learning boredom questionnaire and analyzed using normality, homogeneity, and t-test with IBM SPSS Statistics 25. The results showed a decrease in students’ learning boredom after treatment, with a t-value of 3.315 > t-table 1.734 at a 0.05 significance level. It can be concluded that information services on Mozart music therapy are effective in reducing learning boredom among students.